Pengembangan Campuran Sma (Split Mastic Asphalt) Menggunakan Bahan Rap (Reclaimed Asphalt Pavement) Dan Ijuk - Rif'an, Ahmad (2016)
Using asphalt on pavement in a huge number produce residual wastes of raking asphalt called Reclaimed Asphalt Pavement (RAP). In Falevi's research, RAP characteristics generally met technical qualification, except its gradation. This research aims at identifying proportion effect of RAP and effect of using palm fiber on Split Mastic Asphalt (SMA) performance. The sample has taken from various RAP: 0%, 50%, 100% of hard split total and palm fiber 0%, 0.2%, 0.4% as additional material. According to research results with 70% of hard split fraction, 19.5% of soft split, and 10.5% of filler, optimum asphalt levels gained 7.25%. Variation of specimens indicate that increased levels of RAP caused values of VFWA and flow tend to increase, while values of VMA, VIM, stability, and Marshall Quotient (MQ) tend to decrease. On the contrary, increased levels of palm fiber caused the values of VMA, VIM, stability, and Marshall Quotient (MQ) tend to increase, while the values of VFWA and flow tend to decrease. RAP level that is qualified for SMA grading 0/11 is 42% of total material compound with 0.4% of fiber level.